Using natural biostimulants for enhancing defense response of tomatoes against aphids - Arij Fakraoui; Zayneb Kthiri; Walid Hamada; Ghazi Krida (PLoS ONE, 2026)
To explore alternative methods for insect control, we investigated the effectiveness of natural biostimulants in triggering defense responses against the cotton-melon aphid Aphis gossypii on tomato plants. The tested biostimulants were rosemary essential oil, the fungus Trichoderma harzianum , the PGPR (Plant Growth-Promoting Rhizobacteria) Bacillus subtilis , and a mix of microalgae. Their effects were compared to an untreated control and to the chemical product Bion (a salicylic acid pathway inducer) as a positive control. Tomato seedlings were exposed to aphid infestation at different leaf levels, and aphid colony development was monitored over time. The impact of biostimulants was assessed by counting aphid numbers at 72 h post-infestation. Additionally, aphid fecundity was evaluated in a subsequent trial with potted tomatoes. In parallel, we explored the rapid effects of root-fed biostimulants on aphid populations using hydroponic tomato seedlings. Leaves from plants treated with biostimulants and with the reference product Bion showed a significant reduction in adult aphid population density and reproduction rates compared to untreated controls. Specifically, control plants exhibited higher aphid reproduction rates, which was significantly reduced at 6 days post-infestation. However, no significant differences were observed between treated and control plants beyond this time, indicating that a strong plant defense response was triggered within one week. Our findings clearly demonstrate the great potential of using biostimulants as promising tools for enhancing tomato integrated pest management.